2020
DOI: 10.1021/acs.inorgchem.9b02497
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II) and Nickel(II) Complexes of a PNN Type Ligand as Photoenhanced Electrocatalysts for the Hydrogen Evolution Reaction

Abstract: Hydrogen will be an important energy vector of the future, and improved efficiency in electrohydrolysis will accelerate this transition. In a fundamental study, we have prepared Co­(II) and Ni­(II) complexes of a new PNN type ligand N-((diphenylphosphanyl)­methyl)-2-amino-1,10-phenanthroline (dppmaphen) incorporating the photoactive 1,10-phenanthroline group and the strongly coordinating diphenylphosphine to obtain photoelectrochemical (PEC) catalysts [Co­(dppmaphen)2(NO3)2] (1) and [Ni­(dppmaphen)2Cl]Cl (2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Ar' Ar Yield, % d P , ppm 77 [209,210] -18.5 (CDCl 3 ) 48 [211] -20.4 (CDCl 3 ) 59, [210] 79, [212] 95 [213] -17.4 (DMSO-d 6 ), -18.1 (CDCl 3 ), -18.5 (CDCl 3 ) 87 [212] -16.8 (DMSO-d 6 ) 87 [214] -17.4 (CDCl 3 ) 88 [215] -18.1 (CDCl 3 ) 60 [215] -19.3 (CDCl 3 ) 59, [216] 71, [217] 78 [218] -18.9 (CDCl 3 ), -19.4 (CDCl 3 ), -22.2 (DMSO-d 6 ) 64, [219] 93 [220] -17.1 (CDCl 3 ) 61 [221] -17.2 (CDCl 3 ) 87 [222] -18.6 (CDCl 3 ) 37 [223] -17.8 (CD 2 Cl 2 ) 23 [143] -19.6 (CDCl 3 ) 93 [210] -18.8 (CDCl 3 ) 51 [148] -33.2 (CDCl 3 ) 73 [148] -31.7 (CDCl 3 )…”
Section: Entrymentioning
confidence: 99%
“…Ar' Ar Yield, % d P , ppm 77 [209,210] -18.5 (CDCl 3 ) 48 [211] -20.4 (CDCl 3 ) 59, [210] 79, [212] 95 [213] -17.4 (DMSO-d 6 ), -18.1 (CDCl 3 ), -18.5 (CDCl 3 ) 87 [212] -16.8 (DMSO-d 6 ) 87 [214] -17.4 (CDCl 3 ) 88 [215] -18.1 (CDCl 3 ) 60 [215] -19.3 (CDCl 3 ) 59, [216] 71, [217] 78 [218] -18.9 (CDCl 3 ), -19.4 (CDCl 3 ), -22.2 (DMSO-d 6 ) 64, [219] 93 [220] -17.1 (CDCl 3 ) 61 [221] -17.2 (CDCl 3 ) 87 [222] -18.6 (CDCl 3 ) 37 [223] -17.8 (CD 2 Cl 2 ) 23 [143] -19.6 (CDCl 3 ) 93 [210] -18.8 (CDCl 3 ) 51 [148] -33.2 (CDCl 3 ) 73 [148] -31.7 (CDCl 3 )…”
Section: Entrymentioning
confidence: 99%
“…We [11][12][13][14][15][16]29], and others [17,[19][20][21][22], have previously used Mannich condensations as a versatile method for the synthesis of aminomethylphosphines. Accordingly, two equivalents of Ph 2 PCH 2 OH were reacted with one equivalent of the amine, for 24 h at r.t. under N 2 , yielding the desired phenol-substituted ditertiary phosphines 1a-e and 3 (Scheme 1).…”
Section: Ligand Synthesismentioning
confidence: 99%
“…For a number of years, we [11][12][13][14][15][16], and others [17][18][19][20][21][22], have been interested in aminomethylphosphines, readily amenable by Mannich condensation reactions. Such interest stems from the relative ease of accessing P-monodentate ligands based on a P-C-N linker [11,15,16,19,20,22] or P/P-bidentate derivatives bearing a P-C-N-C-P backbone [12][13][14][17][18][19]21]. Previously, we have shown that the N-arene group can be easily tuned with, for example, various H-bonding donor/acceptor sites based on -CO 2 H/OH groups [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Chelating diphosphines are widely used in transition metal chemistry and can also be susceptible to thermal/chemical induced P−C bond activation at one (or more) metal centres [5]. We [6], and others [7,8],…”
Section: Introductionmentioning
confidence: 99%